Intussuscepted Sigmoid Colonic Lipoma Mimicking Carcinoma Rectum - Roy, Sharmistha; Mondal, Samiron Kumar; Maitra, Tapash Kumar (BIRDEM Medical Journal, 2016)
Adult colorectal intussusception is a relatively rare condition. It is different from that of a child in that, most cases have an organic etiology like a malignant or benign neoplasm. This is a 40 year female patient presenting with passage of blood and mucous per rectum later diagnosed as sigmoidorectal intussusception due to submucous lipoma in sigmoid colon that was protruding through anus giving the appearance of a large polypoid rectal growth. Birdem Med J 2015; 5(1) Supplement: 56-58